????????????????????????????????????????????/
Answer:
x = 17
Step-by-step explanation:
Direct variation is given by
y = kx where k is the constant of variation
-35 = k*7
-35/7 = k
-5 = k
y = -5x
We know y = -85
-85 = -5x
Divide each side by -5
-85/-5 = x
17 =x
Answer:
70
Step-by-step explanation:
60+10=70
Answer:
3 x -3y = -9y
3 x -1 = -3
The factored expression is 3(-3y - 1)
Step-by-step explanation:
All you have to do is -9y / 3 = -3y and -3 / 3 = -1, then put those numbers in parentheses. All of that is multiplied by 3.
The reason is because if you distributed the 3 it would become:
3 * -3y + 3 * -1 = -9y - 3